Call to action as a modern social media marketing tool on Meta Business Suite accounts - Stępień-Kowalik, Klaudia (The phenomena of propaganda and manipulation in the press, radio, television, and internet. Volume II, 2023)
The aim of this article is to present the issue of the potential of social media platforms such as Instagram or Facebook in the marketing activities of enterprises which use social media to promote their own products and services on Meta Business Suite advertising accounts. Brand promotion in social media plays an extremely important role nowadays - companies establish ties with customers in order to persuade interested users to buy a product or choose a specific service. For the purposes of this speech, selected advertisements were analyzed from the perspective of a call to action marketing message, encouraging recipients to take specific action via CTA buttons, also known as "calls to action". They are embedded in three ad formats: single image or video, carousel ads made of up to 10 images or videos, and ads based on instant footage. The main purpose of this work is to examine the effectiveness of call to action as a modern social media marketing tool. Therefore, referring to selected marketing issues, I will use media content analysis, content analysis and critical analysis.